2018
DOI: 10.1001/jamacardio.2018.0510
|View full text |Cite|
|
Sign up to set email alerts
|

Association of Methylation Signals With Incident Coronary Heart Disease in an Epigenome-Wide Assessment of Circulating Tumor Necrosis Factor α

Abstract: We identified and replicated novel epigenetic correlates of circulating TNF-α concentration in blood samples and linked these loci to coronary heart disease risk, opening opportunities for validation and therapeutic applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4
1

Relationship

3
7

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 42 publications
(69 reference statements)
1
25
0
Order By: Relevance
“…PARP9 is involved in the regulation of macrophage activation via pro-inflammatory IFN-γ signalling, which underlies the role of inflammation in the pathogenesis of CHD [47]. Interestingly, a recent study related methylation at this CpG to lower risk of incident CHD, consistent with our findings in incident CVD [48]. cg25103337, mapping to H6PD , which encodes one enzyme involved in the glucose metabolism (pentose phosphate pathway), was not related to any CVRF.…”
Section: Discussionsupporting
confidence: 86%
“…PARP9 is involved in the regulation of macrophage activation via pro-inflammatory IFN-γ signalling, which underlies the role of inflammation in the pathogenesis of CHD [47]. Interestingly, a recent study related methylation at this CpG to lower risk of incident CHD, consistent with our findings in incident CVD [48]. cg25103337, mapping to H6PD , which encodes one enzyme involved in the glucose metabolism (pentose phosphate pathway), was not related to any CVRF.…”
Section: Discussionsupporting
confidence: 86%
“…Circulating concentrations of tumor necrosis factor α, a pro-inflammatory cytokine linked to atherosclerosis, were recently shown to be associated with methylation changes in the immune response-related genes DTX3L-PARP9 and NLRC5. DNA methylation levels of those genes were also shown to negatively correlate with CHD incidence (Aslibekyan et al, 2018). Similarly, a large EWAS meta-analysis on serum C-reactive protein (CRP), an inflammation biomarker predicting heart failure, identified 58 CpG sites related to CRP levels.…”
Section: Cardiovascular Diseasementioning
confidence: 96%
“…Indeed, Mendelian randomization approaches across multiple phenotypes have suggested that reverse causation is more common [6,7] than the causal methylation effect that is often implicitly assumed. One approach to this problem is to examine epigenetic associations with cardiovascular [8,9], and have even uncovered prognostic CpG sites for incident coronary heart disease in the process [10,11]. A few studies looking directly at incident CVD as a binary variable have found relationships with global DNA methylation (as approximated by LINE-1 methylation levels) and with a specific cluster of CpG sites in the ZBTB12 gene [12,13].…”
Section: Introductionmentioning
confidence: 99%